The primrose path - Matas, Carol, 1949- (Winnipeg : Bain & Cox, 1995)
When fourteen-year-old Debbie moves to a new town and Hebrew school following the death of her grandmother, she begins to be uncomfortable with the overly familiar behavior of the Rabbi principal.
Keywords: Sexual abuse -- Fiction; Rabbis -- Fiction; Moving, Household -- Fiction; Schools -- Fiction; Jews -- Canada -- Fiction